ANALYSIS OF COMPETENCE EFFECT, INDEPENDENCE, PLANNING AUDIT, AUDIT SUPERVISION AND AUDIT RESULTS REPORTING ON AUDIT QUALITY IN INSPECTORATE BINJAI CITY WITH AS MOTIVATION MODERATING VARIABLES - rahmayani, rini (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of competency, independence, auditing planning, auditing supervision and auditing result report on the auditing quality in the Inspectorate of Binjai Municipality with motivation as the moderating variable. This is a quantitative research using analytical survey. The population and samples of the research were the government employees serving in the Inspectorate of Binjai Municipality i.e. 50 people, taken by using census method. The data were collected through questionnaires. Descriptive statistical analysis and SEM PLS (Partial Least Square Analysis) were applied as the data analysis method. The analysis was assisted by Smart PLS program. The results of this research demonstrated that competency, independence, auditing planning, auditing supervision, auditing result report and motivation had a significant positive influence on the auditing quality. Motivation as the moderating variable could not moderate the correlation of competency, independence, auditing planning, auditing supervision and auditing result report with the auditing quality in the Inspectorate of Binjai Municipality.